Mitochondrial Quality Control in Aging and Heart Failure: Influence of Ketone Bodies and Mitofusin-Stabilizing Peptides - Thai, Phung N.; Seidlmayer, Lea K.; Miller, Charles; Ferrero, Maura; Dorn, Gerald W.; Schaefer, Saul; Bers, Donald M.; Dedkova, Elena N. (Frontiers in Physiology, 2019)
Aim: Aging and heart failure (HF) are each characterized by increased mitochondrial damage, which may contribute to further cardiac dysfunction. Mitophagy in response to mitochondrial damage can improve cardiovascular health. HF is also characterized by increased formation and consumption of ketone bodies (KBs), which may activate mitophagy and provide an endogenous mechanism to limit the adverse effects of mitochondrial damage. However, the role of KBs in activation of mitophagy in aging and HF has not been evaluated. Methods: We assessed mitophagy by measuring mitochondrial Parkin accumulation and LC3-mediated autophagosome formation in cardiomyocytes from young (2.5 months), aged (2.5 years), and aged rabbits with HF (2.5 years) induced by aortic insufficiency and stenosis. Levels of reactive oxygen species (ROS) generation and redox balance were monitored using genetically encoded sensors ORP1-roGFP2 and GRX1-roGFP2, targeted to mitochondrial or cytosolic compartments, respectively. Results: Young rabbits exhibited limited mitochondrial Parkin accumulation with small ( 1 μm2) puncta. Those small Parkin puncta increased four-fold in aged rabbit hearts, accompanied by elevated LC3-mediated autophagosome formation. HF hearts exhibited fewer small puncta, but many very large Parkin-rich regions (4–5 μm2) with completely depolarized mitochondria. Parkin protein expression was barely detectable in young animals and was much higher in aged and maximal in HF hearts. Expression of mitofusin 2 (MFN2) and dynamin-related protein 1 (DRP1) was reduced by almost 50% in HF, consistent with improper fusion-fission, contributing to mitochondrial Parkin build-up. The KB β-hydroxybutyrate (β-OHB) enhanced mitophagy in young and aging myocytes, but not in HF where β-OHB further increased the number of cells with giant Parkin-rich regions. This β-OHB effect on Parkin-rich areas was prevented by cell-permeable TAT-MP1Gly peptide (thought to promote MFN2-dependent fusion). Basal levels of mitochondrial ROS were highest in HF, while cytosolic ROS was highest in aged compared to HF myocytes, suggesting that cytosolic ROS promotes Parkin recruitment to the mitochondria. Conclusion: We conclude that elevated KB levels were beneficial for mitochondrial repair in the aging heart. However, an impaired MFN2-DRP1-mediated fusion-fission process in HF reduced this benefit, as well as Parkin degradation and mitophagic signaling cascade.